Considerations for a roadmap for the operation of unmanned aerial vehicles (UAV) in South African airspace - Ingham, L. A. (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Electrical and Electronic Engioneering))--Stellenbosch University, 2008.